Social venture creation and the influence of commercial ventures. Issue 3 (7th November 2016) - Kachlami, Habib
Abstract : Purpose: The purpose of this paper is to understand how social and commercial ventures interact with each other. It investigates how the entry, exit and prevalence of commercial ventures in a given region can influence the creation of social ventures. Design/methodology/approach: Market failure theory has been used as a framework for analysing the interaction between social and commercial ventures. The results of the theoretical analysis were further empirically examined using a large-scale database covering all 290 municipalities in Sweden from 1990 to 2014 and applying the panel-corrected standard errors method. Findings: The results of this study, in general, reveal a competition between social and commercial ventures. Its specific results, however, are related to influences that the entry, exit and prevalence of commercial ventures can have on the creation of social ventures. The study's results reveal that while the entry and prevalence of commercial ventures in a region negatively influence the creation of social ventures, commercial ventures' exits have a positive influence. Originality/value: Within social entrepreneurship literature, this is the first study that empirically investigates the influence of commercial ventures' entry and exit on social venture creation and the second study to investigate the influence of commercial ventures' prevalence on social venture creation. It is also the first of such studies in the Swedish context. The study is also unique due to the large-scale database it uses.